Draft Annual Plan 2004-05 Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 2004)
Agriculture & Allied Activities, Rural Development, Special Area Programmes, Irrigation & Flood Control, Energy, Industry & Minerals, Transport, Communications, Science, Technology & Environment, General Economic Services, Social Services, General Services
Government of Pondicherry Planning and Research Department
Government of Pondicherry Planning and Research Department
Keywords: Annual Plan; 2004-05; Statements; Bharat Nirman Programmes; Tribal Sub Plan; Financial Outlays; Transport; Centrally Sponsored Schemes; Externally Aided Projects